Analysis of Microplastics on Sediments in the Waters of Selat Panjang of Tebing Tinggi Subdistrict, Meranti Islands Regency, Riau Province - Pasaribu, Ridwan Saiful Basri; Nedi, Syahril; Elizal, Elizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The study was conducted from March to May 2021 which aims to identify the types, abundance of microplastics and compare the abundance of microplastics between stations in the waters of the Long Strait of High Cliff Subdistrict. Survey methods are applied and PVC pipes are used to collect sediment samples from three different stations with three sampling points at each station. The types of microplastics found are fragments with the most jumblah with film and fiber. The most widely found types are fragments, followed by film and fiber. The abundance of microplastics at Tanjung Harapan Port (5900.00 partkels /kg of dry sediment) is higher than the mouth of the Dorak coastal river (5306.67 partkels/kg of dry sediment) and Banglas Village Mangrove Ecotourism (4120.00 partikels/kg of dry sediment). The results showed that the abundance of microplastics between stations differed significantly. Microplastic differences based on further independent test samples t-test showed that each station compared to mangrove ecotourism area will be significantly different, while between Tanjung Harapan Port and the mouth of the Dorak coastal river showed no significant difference